The Four Axes of Palermo’s Commerce: a Geographical Perspective - Giovanni Messina; Gaetano Sabato (Bollettino della Società Geografica Italiana)
Commercial dynamics within a city represent an excellent observatory desk to study urban transformation processes. These dynamics reflect the verticality and horizontality relational system, but also the exchanges and reciprocation of the cultural and socio-economic relations. From a geographical perspective it is interesting to detect cultural, social and economic changes both permanent and in evolution which constitute the urban pattern and shape its viability. This work originates in 2015 within the PRIN project (Relevant Interest National Project) “Commerce, consumption and the city: practices, planning and governance for urban inclusion, resilience and sustainability” which has studied some relevant commerce dynamics in Italian main cities. Here we focus on the case of Palermo, by analysing four important streets in the city center: via Maqueda, via Ruggero Settimo, viale della Libertà and via Lincoln. They represent significant cut outs of how consumers’ habits have developed in Palermo and have strongly characterized the present urban landscape by establishing a complex network of relations which shape the pattern of the city. By employing both a diacronical and synchronical approach, on one hand we analyse the evolution of the four axes. On the other hand, we illustrate the results of the research carried out by using questionnaires aimed to reveal the present conditions of the shops taking place through the business owners’ perception.